La lettura dei bilanci delle Organizzazioni di Volontariato toscane nel biennio 2004-2005 - Luca Bagnoli (Strumenti per la didattica e la ricerca, 2007)
This study, emerging from workshop activity carried out as part of the course on ECONOMY AND ADMINISTRATION OF CO-OPERATION AND NON-PROFIT, represents an examination of the economic-financial dimension of the work of the Tuscan voluntary organisations. It is inserted within an articulated research process devoted to an analysis of the accountability of these third sector agents, in the awareness that voluntary work has always been an important factor in civil progress. More specifically, the economic and financial information made available to the provinces as a result of the obligation on the voluntary organisations to deposit the annual financial statement has been fully exploited. This compliance has thus been transformed from a mere bureaucratic procedure into an opportunity for a collective cognitive enrichment through collection at regional level, reclassification and the aggregate analysis of the economic and financial data relating to the management reports (profit and loss accounts) of the voluntary organisations for 2004-2005. This has made it possible to underscore the nature and provenance of the economic and financial resources that accrue annually to such bodies, as well as the principal productive factors "consumed" in the performance of their activities.